HOT-Fit Evaluation of a Laboratory Management Information System in Vocational Higher Education - A. Labib Fardany Faisal; Aries Alfian Prasetyo; Akhmad Arif Kurdianto; Ahmad Mustofa (Information Technology and Science (ITScience), 2026)
The Laboratory and Workshop Information System named SIABEL at Politeknik Negeri Madura has been operational since January 2024, providing five core modules: Catalogue, Usage, Procurement, Inventory Verification, and Reporting. Despite more than one year of operation, active adoption remains at approximately 40% of institutional laboratory and workshop units. This study evaluates the factors influencing system adoption using the HOT-fit (Human, Organization, Technology–fit) framework, identifies functional and structural gaps, and proposes a phased system development plan grounded in evaluation findings. Data were collected via a structured five-point Likert-scale questionnaire administered to 119 respondents across four role groups — Students (74.8%), Laboratory Technicians (10.9%), Laboratory and Workshop Heads (8.4%), and Supervising Lecturers (5.9%) — drawn from four academic departments. The 44-item instrument was confirmed valid (r = 0.793–0.921) and reliable across all nine HOT-fit constructs (Cronbach's ? = 0.901–0.937). Descriptive analysis shows all constructs scored in the Good category (overall means 3.74–3.83), establishing that the adoption gap is not attributable to system quality failure but to three structural conditions: a configuration mismatch between the system and the Department of Health's laboratory workflows, functional gaps that reduce the net benefit perceived by Laboratory Technicians, and weak institutional governance. A 14-initiative, three-phase development plan is proposed, prioritizing a health laboratory configuration module, an automated notification engine, and a structured onboarding program as immediate interventions.